Podejście projektowe jako sposób zarządzania placówkami służby zdrowia - Kacała, Joanna (Project approach as a way of medical facilities management, 2005)
In the article its author presents possibilities of introducing of projects management in medical facilities. Starting from an analysis of crucial factors of success which are specific for hospitals, the author describes how the project approach can optimize functioning of medical facilities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 253-260